Increased blood pressure variability in pheochromocytoma compared to essential hypertension patients - Zelinka, Tomás; Strauch, Branislav; Petrák, Ondrej; Holaj, Robert; Vranková, Alice; Weisserová, Hana; Pacák, Karel; Widimský, Jiri (Journal of hypertension, 2005)
OBJECTIVE: Catecholamines are responsible for short and long-lasting blood pressure (BP) elevations in pheochromocytoma. We investigated whether in patients with pheochromocytoma this catecholamine excess would result in higher BP variability in comparison with patients suffering from essential hypertension (EH). DESIGN: We examined retrospectively 54 (26 treated with alpha1-blockers) patients with pheochromocytoma (30 patients also investigated after tumour removal) and 108 (42 treated with alpha1-blockers) patients with EH. They all underwent 24-h ambulatory BP monitoring. To assess the BP variability, coefficient of BP variability (SD of average BP/average BP) was used. RESULTS: In subjects with pheochromocytoma, a higher coefficient of BP variability was shown compared with EH during the 24-h period (0.12 +/- 0.03 versus 0.10 +/- 0.02, P = 0.003 for systolic BP in the treated group) and mainly during the daytime (0.11/0.13 +/- 0.04/0.03 versus 0.09/0.11 +/- 0.03/0.04, P = 0.007/0.06 for systolic/diastolic BP in the untreated group and 0.12/0.13 +/- 0.04/0.04 versus 0.09/0.12 +/- 0.04/0.02, P < 0.001/0.01 in the treated group). Tumour removal resulted in a decrease of the previously increased 24-h (0.11 +/- 0.03 versus 0.10 +/- 0.03, P = 0.04) and daytime (0.11 +/- 0.03 versus 0.09 +/- 0.03, P = 0.03) coefficient of systolic BP variation. Twenty-seven subjects with pheochromocytoma and inverted circadian BP rhythm (night-time BP > daytime BP) had a significantly higher 24-h (0.13 +/- 0.03 versus 0.10 +/- 0.03, P < 0.001 for systolic BP) and daytime coefficient of BP variation (0.13/0.15 +/- 0.04/0.03 versus 0.09/0.12 +/- 0.02/0.02, P < 0.001/<0.001) and also a higher occurrence of the isolated excretion of norepinephrine (14 versus seven subjects, P = 0.05) compared with the 27 subjects with pheochromocytoma without inverted circadian BP rhythm. CONCLUSION: The excess of catecholamines in patients with pheochromocytoma is associated with higher long-term BP variability in comparison with patients suffering from EH especially in subjects with inverted circadian BP rhythm. Tumour removal resulted in the amelioration of the previously increased BP variability.
Keywords: výsledek terapie; feochromocytom; Pheochromocytoma; Male; hypertenze; retrospektivní studie; Catecholamines; Heart Rate; noradrenalin; Norepinephrine; Adult; dospělí; mužské pohlaví; srdeční frekvence; Adrenal Gland Neoplasms; Hypertension; Adrenergic alpha-Agonists; cirkadiánní rytmus; Circadian Rhythm; Treatment Outcome; agonisté adrenergních alfa-receptorů; nádory nadledvin; katecholaminy; lidé; krevní tlak; ženské pohlaví; Humans; Blood Pressure; ambulantní monitorování krevního tlaku; Retrospective Studies; Blood Pressure Monitoring, Ambulatory; Female; lidé středního věku; Middle Aged